Early Membrane Responses to Magnetic Particles are Predictors of Particle Uptake in Neural Stem Cells. (29th January 2015) - Fernandes, Alinda R.; Adams, Christopher F.; Furness, David N.; Chari, Divya M.
<x xml:space="preserve">Abstract</x> Magnetic particles (MPs) offer several advantages for neural cell therapy, but limited particle uptake by neural cells is a barrier to translation. It is recently proved that tailoring particle physicochemical properties (by enhancing their iron content) dramatically improves uptake in neural stem cells (NSCs)—a major transplant population. High‐throughput screening of particles with varying physicochemical properties can therefore aid in identifying particles with optimal uptake features, but research is hampered by the lack of simple methodologies for studying neural cell membrane responses to nanoparticle platforms. A high‐resolution–high throughput method has been used to study early membrane responses of primary rodent NSCs to particles of variant magnetite loading, to attempt to correlate these responses with known particle internalization profiles. Membrane imaging is enhanced through sequential staining with osmium (O) and thiocarbohydrazide (T), a method termed OTOTO, combined with field‐emission scanning electron microscopy (FESEM). A five‐point classification system was used to systematically evaluate early MP‐induced membrane responses to particles possessing distinct physicochemical properties. Significantly different profiles of membrane activation were noted that correlate with particle uptake profiles. It is suggested that our method can serve as a valuable predictor of particle internalization in neural cells for diverse particle platforms.